Peran Bundo Kanduang Dalam Melestarikan Adat Istiadat Pada Masyarakat Minang Di Kota Medan - Nur Wulan Rahmadani; Achiriah Achiriah (Jurnal Pendidikan Indonesia (JOUPI), 2024)
Indonesia has different traditional and cultural structures such as those in Minangkabau. By having a matrilineal system, namely where the lineage follows the mother’s liniage. The existence of this matrilineal system is one of the strong reasons that the Minangkabau people have implemented gender equality in Minangkabau culture. Bundo Kanduang is also called “limpapeh rumah nan gadang, sumarak in nagari”, mother as bundo kanduang is a symbol of honor within the clan and within the nagari. This research is qualitative research with a historical approach. These data collection techniques include observation, documentation, and interviews. The informations in this research were 2 people, namely Mr. Yunan Sirhan and Mrs. Rahma. The results obtained from this research are that the bundo kanduang in the city of Medan was formed on September 13, 2017. The role of the Bundo Kanduang in customs is, manure alua nan luruih (according to a straight path), managing the road nan pasa (taking the market road), maintaining the harato and pusako (looking after property and inheritance) looking after children.